Financing Decisions and Green Accounting: The Moderating Role of Profitability - Christiani, Irma; Saragih, Afni Eliana (E-Jurnal Akuntansi; Vol 34 No 12 (2024), 2024)
Environmental management has emerged as a pressing global concern, prompting governments worldwide to mandate the adoption of environmentally sustainable practices, commonly referred to as green accounting. This study examines the effects of debt financing and equity financing decisions on green accounting practices while also investigating the moderating role of profitability in these relationships. The research utilizes secondary data collected from manufacturing firms in the basic industry and chemical sectors listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. A panel data regression analysis with moderation effects was employed, with preliminary testing conducted to determine the most appropriate econometric model: Fixed Effect Model (FEM), Common Effect Model (CEM), or Random Effect Model (REM). The findings reveal that debt financing negatively impacts green accounting practices, while equity financing has a significant positive effect. However, profitability was not found to moderate the relationship between financing decisions and green accounting. These results underscore the distinct influences of financing strategies on corporate environmental practices and suggest that profitability alone may not enhance the integration of green accounting within financing decisions.